Action! : interviews with directors from classical Hollywood to contemporary Iran - Morris, Gary, 1951- (London ; New York : Anthem Press, 2009)
'Action!' draws on the very best published and unpublished interviews of the 'Bright Lights Film Journal', and contains many gems, including the last ever interview given by Francois Truffaut, four months before he died.
Introduction: the art and craft of interviewing / by Bert Cardullo -- Angel in exile: Allan Dwan / by Howard Mandelbaum and Gary Morris -- "An unhappy happy end": Douglas Sirk / by Michael Stern -- Somebody up there likes me: Robert Wise / C. Jerry Kutner -- "The greatest movie the world has never seen": Peter Bogdanovich and Joseph McBride on Orson Welles' The other side of the wind / by Damien Love -- "Plant your feet and tell the truth": Clint Eastwood / by Tony Macklin -- Manderlay: Lars von Trier / by Karin Luisa Badt -- 20 angosht (20 fingers): Mania Akbari / by Dorna Khazeni -- I am a sex addict: Caveh Zahedi / by Peter Rinaldi -- Caché (Hidden): Michael Haneke / by Karin Luisa Badt -- Sweet soul music: Melvin and Mario Van Peebles / by Damon Smith -- Nearer my Corman to thee: Roger Corman, Bruce Dern and David Carradine / by Damien Love -- An actionist begins to sing: Otto Muehl / by Andrew Grossman, tran. by Robert Mark Grossman -- "They're panicking, look at them!" the brothers Quay / by Damon Smith -- Dialogues with madwomen: Allie Light / by Gary Morris -- Shut up & sing: Barbara Kopple / by Damon Smith -- "For a kind of pleasure": Federico Fellini / by Toni Maraini, trans. by A.K. Bierman -- Transcendental style, poetic precision: Robert Bresson / by Bert Cardullo -- "The fruitful tree bends": Abbas Kiarostami / by Bert Cardullo -- Alter ego, autobiography and auteurism: François Truffant / by Bert Cardullo.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Motion picture producers and directors -- Interviews; Motion pictures -- Production and direction; Producteurs et réalisateurs de cinéma -- Entretiens; Cinéma -- Production et réalisation.; PERFORMING ARTS -- Film & Video -- Reference; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Direction & Production; Motion picture producers and directors; Motion pictures -- Production and direction; Filmregisseur; Film; Interviews